Effect of Poly(amine)s on the Redox Properties of Carboxymethylcellulose and Ferrocene‐modified Poly(amine) Layer‐by‐Layer Films. Issue 2 (28th July 2015) - Aikawa, Yu; Watanabe, Takumi; Minaki, Daichi; Takahashi, Shigehiro; Wang, Baozhen; Anzai, Jun‐ichi
Abstract: Multilayer films consisting of carboxymethylcellulose (CMC) and ferrocene‐modified poly(ethyleneimine) (Fc‐PEI) or poly(allylamine hydrochloride) (Fc‐PAH) were successfully prepared on a gold electrode to examine their redox properties. The redox current of (Fc‐PEI/CMC)n film‐coated electrodes increased with the number of layers, while the (Fc‐PAH/CMC)n film‐coated electrodes exhibited increased response only for the first eight bilayers. The (Fc‐PEI/CMC)n and (Fc‐PAH/CMC)n films deposited on the surface of Fc‐free multilayer film‐coated electrodes also showed a redox response. The (PEI/CMC)5 film‐coated electrode showed redox responses in Fc‐PEI and Fc‐PAH solutions, confirming the uptake of the Fc‐polymers in the inner film. In contrast, the uptake of the Fc‐polymers in the (PAH/CMC)5 film was severely suppressed, suggesting that different permeability of (PEI/CMC)5 and (PAH/CMC)5 films. Abstract :